Shadow Economic Activity as a Threat to the Economic Security of Commercial Organizations - Alexey M. Shunaev; Vladimir M. Shunaev (Евразийская интеграция: экономика, право, политика)
The present article considers the current rate of shadow economic activity in the Russian Federation, its causes and factors determining its development. The comparison of changes in indicators of the shadow economy with macroeconomic indicators is given. Conclusions are drawn concerning the causes determining the shadow economic activity and features of this activity in the territory of the Russian Federation.